2019
DOI: 10.1001/jamainternmed.2018.5118
|View full text |Cite
|
Sign up to set email alerts
|

Association of Team-Based Primary Care With Health Care Utilization and Costs Among Chronically Ill Patients

Abstract: IMPORTANCE Empirical study findings to date are mixed on the association between team-based primary care initiatives and health care use and costs for Medicaid and commercially insured patients, especially those with multiple chronic conditions. OBJECTIVE To evaluate the association of establishing team-based primary care with patient health care use and costs. DESIGN, SETTING, AND PARTICIPANTS We used difference-indifferences to compare preutilization and postutilization rates between intervention and compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 27 publications
(55 reference statements)
1
54
0
Order By: Relevance
“…The perceptions of the respondents in this study add support to the growing body of research showing that team-based care improves the safety and quality of primary care delivery [4,5,6]. Given this linkage between teamwork and care quality and safety, it is not surprising that Poghosyan and colleagues found that both physicians and nurse practitioners report greater satisfaction with their work in more collaborative environments.…”
supporting
confidence: 61%
“…The perceptions of the respondents in this study add support to the growing body of research showing that team-based care improves the safety and quality of primary care delivery [4,5,6]. Given this linkage between teamwork and care quality and safety, it is not surprising that Poghosyan and colleagues found that both physicians and nurse practitioners report greater satisfaction with their work in more collaborative environments.…”
supporting
confidence: 61%
“…We then calculated inverse probability of treatment weights (IPTWs) using the estimated propensity scores. 28 …”
Section: Methodsmentioning
confidence: 99%
“…We then calculated inverse probability of treatment weights (IPTWs) using the estimated propensity scores. 28 Outcomes MHQP also produces the Patient Experience Survey (PES) and Clinical Quality (CQ) datasets, which provide practicelevel quality measures based on survey and claims data for patients enrolled in any 1 of 5 commercial health plans. 38 These 5 plans comprised the majority of the commercially insured population in Massachusetts (eg, approximately 70% of the state in 2016).…”
Section: Identification Of Aic and Comparison Practicesmentioning
confidence: 99%
“…Most of the research focused on identifying the factors that were present in practices which resulted in TBC for diabetes ( 24 ). Therefore, there is practically no empirical data on the effect of the organizational factors cited on TBC for diabetes ( 6 , 7 , 26 , 35 37 , 39 , 43 46 , 48 , 51 , 53 , 57 , 58 ). It is important to note that the three studies that did not see improved outcomes had a focus on Structure and Processes (the only unifying factor) and none focused on Governance ( 28 , 47 , 54 ).…”
Section: Resultsmentioning
confidence: 99%